1991
DOI: 10.1063/1.106211
|View full text |Cite
|
Sign up to set email alerts
|

Absorption redshift in TiO2 ultrafine particles with surfacial dipole layer

Abstract: It is found that the TiO2 ultrafine particles (UFP) coated with a layer of stearic acid radicals had a significant red shift of their absorption band edge and clear photoluminescence at room temperature (RT), which are in contrast with that of bulk TiO2 and naked TiO2 UFP. It was concluded that these results are related to the self-trapped exciton absorption due to the interfacial dipole layer of stearic acid radicals on the TiO2 UFP surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 21 publications
2
54
1
Order By: Relevance
“…Absorption at long wavelength is often observed in titanates (6), which is assigned to the defect center of a titanium octahedron caused by oxygen vacancies (9). Absorption at long wavelength, which is called the absorption red shift, was also observed by Zou et al with TiO ultrafine particles coated with a surface dipole layer (3,7). The authors attributed the absorption red shift to a dipole layer that induced an attracting potential to electrons inside the UFP and led to the reduction of the band gap of the UFP.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Absorption at long wavelength is often observed in titanates (6), which is assigned to the defect center of a titanium octahedron caused by oxygen vacancies (9). Absorption at long wavelength, which is called the absorption red shift, was also observed by Zou et al with TiO ultrafine particles coated with a surface dipole layer (3,7). The authors attributed the absorption red shift to a dipole layer that induced an attracting potential to electrons inside the UFP and led to the reduction of the band gap of the UFP.…”
Section: Resultsmentioning
confidence: 93%
“…De Haart et al (6) studied the photoluminescence of many titanates and discussed the self-trapped exciton emission from titanates. Recently, Zou et al (3,7) reported that titania ultrafine particles coated with a surface dipole layer exhibited an absorption red shift, self-trapped states, and phonon localization. In this paper, we investigate the electronic states of TiO UFP through luminescence spectra and report some new phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In certain systems, electron-phonon coupling could be strong enough to overcome the spatial confinement to determine the energy of excitons. It determines or modifies the effective mass of carriers and the style of carrier scattering by the lattice, leading to a red-shift of the emission band 29,30 . In addition, we have also observed that the absorption range of the Mn-CeO 2 submicrorods is wider than that of the pure CeO 2 particles.…”
Section: Resultsmentioning
confidence: 99%
“…The surface additives may be either organic such as dyes [137] and surfactants [138] or inorganic such as metallic ions and clusters [139,140] or metal oxides [141]. For bulk doping of TiO 2 , the most studied route is an n-type self-doping associated to the presence of Ti 3+ ions in the lattice.…”
Section: Photon Adsorptionmentioning
confidence: 99%